Characterization of a polymer-infiltrated ceramic-network material - Della Bona, Alvaro; Corazza, Pedro H. [UNESP]; Zhang, Yu (Elsevier B.V., 2014)
Objectives: To characterize the microstructure and determine some mechanical properties of a polymer-infiltrated ceramic-network (PICN) material (Vita Enamic, Vita Zahnfabrik) available for CAD-CAM systems.Methods. Specimens were fabricated to perform quantitative and qualitative analyses of the material's microstructure and to determine the fracture toughness (K-Ic), density (rho), Poisson's ratio (nu) and Young's modulus (E). K-Ic was determined using V-notched specimens and the short beam toughness method, where bar-shaped specimens were notched and 3-point loaded to fracture. rho was calculated using Archimedes principle, and nu and E were measured using an ultrasonic thickness gauge with a combination of a pulse generator and an oscilloscope.Results. Microstructural analyses showed a ceramic- and a polymer-based interpenetrating network. Mean and standard deviation values for the properties evaluated were: K-Ic = 1.09 +/- 0.05 MPa m(1/2), rho = 2.09 +/- 0.01 g/cm(3), nu = 0.23 +/- 0.002 and E = 37.95 +/- 0.34 GPa.Significance. The PICN material showed mechanical properties between porcelains and resin-based composites, reflecting its microstructural components. (C) 2014 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Polymer-infiltrated ceramic-network; Microstructure; Short beam toughness; Young's modulus; Poisson's ratio